2014
DOI: 10.4049/jimmunol.1300096
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Are More Potent Immune Suppressors Ex Vivo Than Immature Myeloid-Derived Suppressor Cells Induced by Metastatic Murine Mammary Carcinomas

Abstract: Myeloid-derived suppressor cells (MDSCs) are emerging as potential promoters of metastatic tumor growth, and there is interest in targeting immature MDSCs by inducing their differentiation into more mature myeloid cells. We used all-trans retinoic acid (ATRA) to differentiate MDSCs in mice bearing metastatic 4T1 or 4TO7 murine mammary tumors, and assessed the immune-suppressive mechanisms and potencies of different myeloid cell subpopulations. Metastatic mammary tumors induced the accumulation of distinct popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 49 publications
7
35
0
Order By: Relevance
“…M-MDSCs are more immunosuppressive than G-MDSCs [22], and we previously reported that macrophages infiltrating the lungs of 4T1 tumor-bearing mice are potently immunosuppressive [35]. Importantly, the decrease of M-MDSCs and macrophages in the lungs after primary 4T1 tumor resection (Fig.…”
Section: Targeting Mdscs With Gemcitabinementioning
confidence: 79%
See 2 more Smart Citations
“…M-MDSCs are more immunosuppressive than G-MDSCs [22], and we previously reported that macrophages infiltrating the lungs of 4T1 tumor-bearing mice are potently immunosuppressive [35]. Importantly, the decrease of M-MDSCs and macrophages in the lungs after primary 4T1 tumor resection (Fig.…”
Section: Targeting Mdscs With Gemcitabinementioning
confidence: 79%
“…Clinical studies have demonstrated the efficacy of pharmacological strategies to reduce MDSC number (e.g., sunitinib) [59], to inhibit MDSC suppressive function (e.g., sildenafil) [60], or to differentiate MDSCs into mature myeloid cells (e.g., all-trans retinoic acid or 25hydroxyvitamin D 3 ) [28][29][30] in a variety of human cancers. We have previously shown that ATRA-mediated differentiation of MDSCs can promote metastatic tumor growth by generation of highly immunosuppressive macrophages [35], and therefore, strategies to target or inhibit MDSCs may produce more predictable outcomes. Directly targeting MDSCs with 5-fluorouracil [61] or gemcitabine [62] in various murine models of cancer significantly enhances T cell-dependent antitumor immunity, suggesting that therapeutics which target MDSCs may work synergistically with T cell-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DCs are reportedly more efficient at T-cell priming than TAMs, macrophages can also prime CD8 þ T cells to generate cytotoxic effector cells and CD8 þ T-cell memory in vivo (32,35). Moreover, tumorigenic TAMs are extremely potent immunosuppressors both individually and through sheer numbers (32,36,37). For example, tumor-infiltrating CD8 þ T cells mostly come into contact with TAMs because of their high frequency, and TAMs can directly induce CD8 þ T-cell apoptosis and physically restrict CD8 þ T cells from reaching their target cells ) 32 , 38 , 39…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the potent immunosuppressive functions of macrophages and support the development of therapeutic strategies to enhance antitumor immunity by targeting inhibitory myeloid cells as a collective group. 12 Moreover, in analogy to the M1/M2 polarization in macrophages, MDSCs also show an M1/M2 classification in the tumor microenvironment. Different studies have shown that MDSCs present within the tumor microenvironment exhibit M2 characteristics, which accelerates tumor growth which is mediated by enhanced arginase activity, an increased secretion of immunosuppressive cytokines and the induction of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%